Intraductal carcinoma of the prostate in prostate biopsy samples: correlation with aggressive pathological features after radical prostatectomy and prognostic value in high-risk prostate cancer - Zhu, Sha (Asian J Androl, 2019)
Intraductal carcinoma of the prostate (IDC-P) is an aggressive pathological pattern of prostate cancer (PCa). We investigated the association of IDC-P in prostate biopsy (PBx) with several pathological features after radical prostatectomy (RP) and its prognostic value in high-risk PCa. A total of 418 patients with high-risk PCa after RP were included in this study. IDC-P and its architectural patterns were identified according to the 2016 World Health Organization Classification. Chi-squared test and logistic regression were used to investigate the correlation between IDC-P and post-RP pathological features. Kaplan–Meier curves and Cox regression were applied to explore the prognostic value of IDC-P. IDC-P was identified in PBx in 36/418 (8.6%) patients. Logistic regression indicated that IDC-P in PBx was independently associated with several pathological features of RP, including Gleason score 8–10 (P < 0.001), seminal vesicular invasion (P < 0.001), and pathological T (pT) 3a (P = 0.043). Patients with IDC-P in PBx manifested poorer biochemical-free survival (BFS) than those without IDC-P (37.47 months vs not reached, P < 0.001). The addition of IDC-P in several prognostic nomograms could improve the predictive accuracy of these tools. We conclude that IDC-P in PBx is positively associated with several aggressive pathological features after RP in high-risk PCa. In addition, IDC-P in PBx could effectively predict the BFS of high-risk PCa patients after RP.